Factors of Tenure Security for Legal Landholders in Urban Areas: The Case of Bahir Dar City, Ethiopia - Prosper Turimubumwe; Adane Mehari; Behailu Melesse (Journal of African Real Estate Research, 2022)
This study examines the relationship between the dependent variable that is ‘feeling of tenure security’ of landholders in Bahir Dar city and the possible determinant factors (independent variables) such as ‘land use type of a parcel’, ‘building type constructed on a parcel’, ‘adequacy of legal provisions’, ‘institutional capacity’, ‘awareness of the landholder about the existing legal provisions of land tenure’, and ‘location of the parcel’ derived from different empirical evidences and practices. And the study also explores the perceptions of the landholders of Bahir Dar city about their land tenure security. Both quantitative and qualitative data were collected through desk review, observation, structured and semi-structured interview. Content analysis for reviewed books and articles was applied. Also, inferential statistics and descriptive analysis of data for all independent and dependent variables were used to analyse the quantitative data. Additionally, critical examination of respondents’ personal perceptions about tenure security on the area was used to analyse the qualitative data. The results showed that the aggregate contribution of those considered independent variables were 74.3% to the effect on feeling of tenure security. It is also revealed that there are five significant predictor variables for felling of tenure security in Bahir Dar city.  But ‘building type’ is the most significant determinant of all variables. Contrary to the empirical evidence the results indicate that awareness of legal provision correlated negatively with security feeling. This study found that the feeling of tenure security for landholders in Bahir Dar city are not much affected by ‘land use type of a parcel’, ‘institutional capacity’, and ‘location of the parcel’. Rather other factors like noise, misbehaviour of neighbours, projected road upgrading, heavy traffic and accidents may push someone to feel insecure and leave the place.